Down-Regulation of Phosphoenolpyruvate Carboxylase Kinase in Grapevine Cell Cultures and Leaves Is Linked to Enhanced Resveratrol Biosynthesis - Elías Hurtado-Gaitán (MDPI AG, 2021)
In grapevine, trans-Resveratrol (tR) is produced as a defence mechanism against stress or infection. tR is also considered to be important for human health, which increases its interest to the scientific community. Transcriptomic analysis in grapevine cell cultures treated with the defence response elicitor methyl-β-cyclodextrin (CD) revealed that both copies of PHOSPHOENOLPYRUVATE CARBOXYLASE KINASE (PPCK) were down-regulated significantly. A role for PPCK in the defence response pathway has not been proposed previously. We therefore analysed the control of PPCK transcript levels in grapevine cell cultures and leaves elicited with CD. Moreover, phosphoenolpyruvate carboxylase (PPC), stilbene synthase (STS), and the transcription factors MYB14 and WRKY24, which are involved in the activation of STS transcription, were also analysed by RT-qPCR. The results revealed that under CD elicitation conditions PPCK down-regulation, increased stilbene production and loss of PPC activity occurs in both tissues. Moreover, STS transcripts were co-induced with MYB14 and WRKY24 in cell cultures and leaves. These genes have not previously been reported to respond to CD in grape leaves. Our findings thus support the hypothesis that PPCK is involved in diverting metabolism towards stilbene biosynthesis, both for in vitro cell culture and whole leaves. We thus provide new evidence for PEP being redirected between primary and secondary metabolism to support tR production and the stress response.